Pengaruh Merek Dagang dan Negara Asal (County of Origin) terhadap Sikap Konsumen dalam Memilih Produk Handphone - Putri, Helva Diansyah; Imsar (Jurnal Informatika Ekonomi Bisnis, 2023)
Consumer attitudes are closely related to the purchase of a product, a brand that becomes a product identity is very influential on the image of the brand. This study aims to determine the effect of brands and also country of origin on consumer attitudes in choosing handphone products for students of the Faculty of Islamic Economics and Business (FEBI), State Islamic University of North Sumatra (UINSU). The population in this study was 1,128 people and a sample of 93 FEBI students in class 2019. The technique used in this study was a random sampling technique. And the data analysis uses multiple linear regression, but before carrying out the regression it is necessary to test between variables using the classic assumption test, then do the t test and f test to find out whether there is influence of trademarks and country of origin on consumer attitudes in choosing handphone products. In this study, the results of multiple linear regression analysis contained in the coefficient of determination table can be seen that the R Square is 0.729 or 72.9%. This means that 72.9% of the independent variables (trademarks and country of origin) affect the dependent variable (consumer attitudes). In this research, trademarks have a more significant effect on explaning the dependent variabel (consumer attitude) compared to the country of origin, this is because trademarks are the most important thing that consumers will see in choosing the product they want or need.